Influence of specimen size and orientation on the mechanical properties of laboratory compacted asphalt specimens - Iwama, Masahiko (2009)
It is always desirable for laboratory compaction to simulate actual site compaction in terms of the volumetric proportions, aggregate structure and mechanical properties of the compacted asphalt mixture, when specimens are manufactured, especially for mixture design. However, finding a laboratory compaction method that is able to achieve this requirement for all asphalt mixture types is in most cases extremely difficult. Some of the reasons for this lack of agreement between site and laboratory compaction include the influence of laboratory factors such as specimen geometry and size, mould confinement and compaction mechanism. Therefore, this study examines the effect of these factors on the volumetric proportions, aggregate matrix and mechanical properties of a typical UK continuously graded asphalt mixture with a maximum aggregate size of 28 mm.